Efeitos dos quimioterápicos taxanos no equilíbrio postural e na marcha de mulheres com neoplasia de mama - Baldissera, Camila (2023)
Introduction: Chemotherapy (CT) is one of the pillars for the treatment of mammary neoplasia (MN), but it may go through the endothelium and cause adverse effects, such as deficits in postural balance (PB). Taxanes may be found among chemotherapeutical drugs used in the antineoplastic regime, but they present the risk of peripheral neuropathy induced by chemotherapy (NPIQ) and may lead to worse postural control in women with MN. Objective: To investigate the effects of taxanes in PB and in gait after the treatment for MN. Methodology: Comparative observational, transversal, and quantitative study. The sample has been divided into two groups – chemotherapy (ChG), women aged 18 to 59 years with a diagnosis of MN who have realized treatment based on taxanes, matched by age range and body mass index; and control group (CG), women not exposed to CT. In the article I, the values of average and Timed Up and Go test (TUG) SD of the ChG (n=26; 8,93 ± 1,66s) and CG (n=26; 6,90 ± 1,04s) have been evaluated. For article II, the mean and SD values of the latency P13 of the right Vestibular Myogenic Evoked Potential (VEMP) of ChG (n=25; 16,96 ± 1,53s) and CG (n=25; 17,85 ± 1,35s) were analyzed. The participants were evaluated after the end of the chemotherapy treatment through: anamnesis, Antineoplastic Induced Neurotoxicity Questionnaire, TUG, Dynamic Foam Laser Posturography, and VEMP. Results: there was a significant difference in the comparison of TUG time between the groups, with worse execution time for GQ. In the sensory analysis, all variables were significant between the groups, with worse performance for the ChG, except the visual system. There was a moderate negative correlation between values of the Sensory Organization Test (SOT) I and TUG in ChG. The waves were present in all VEMP variables in both groups. Latencies in cervical VEMP (cVEMP) were significantly lower in ChG. Numbness, tingling, and heavy legs were the most reported and highly impactful symptoms. Also, an educational booklet was made, related to chemotherapy treatment and its repercussions on PB, used as a mediator in the health education process. Conclusion: Women with MN treated with taxan chemotherapeutical drugs may present impairment in PB, through negative effects on somatosensory (proprioceptive) and vestibular systems and gait alteration.